Bilirubin-Induced Oxidative Stress Leads to DNA Damage in the Cerebellum of Hyperbilirubinemic Neonatal Mice and Activates DNA Double-Strand Break Repair Pathways in Human Cells. (26th November 2018) - Rawat, Vipin; Bortolussi, Giulia; Gazzin, Silvia; Tiribelli, Claudio; Muro, Andrés F.
Abstract : Unconjugated bilirubin is considered a potent antioxidant when present at moderate levels. However, at high concentrations, it produces severe neurological damage and death associated with kernicterus due to oxidative stress and other mechanisms. While it is widely recognized that oxidative stress by different toxic insults results in severe damage to cellular macromolecules, especially to DNA, no data are available either on DNA damage in the brain triggered by hyperbilirubinemia during the neonatal period or on the activation of DNA repair mechanisms. Here, using a mouse model of neonatal hyperbilirubinemia, we demonstrated that DNA damage occurs in vivo in the cerebellum, the brain region most affected by bilirubin toxicity. We studied the mechanisms associated with potential toxic action of bilirubin on DNA in in vitro models, which showed significant increases in DNA damage when neuronal and nonneuronal cells were treated with 140 nM of free bilirubin (Bf), as determined by γ H2AX Western blot and immunofluorescence analyses. Cotreatment of cells with N-acetyl-cysteine, a potent oxidative-stress inhibitor, prevented DNA damage by bilirubin, supporting the concept that DNA damage was caused by bilirubin-induced oxidative stress. Bilirubin treatment also activated the main DNA repair pathways through homologous recombination (HR) and nonhomologous end joining (NHEJ), which may be adaptive responses to repair bilirubin-induced DNA damage. Since DNA damage may be another important factor contributing to neuronal death and bilirubin encephalopathy, these results contribute to the understanding of the mechanisms associated with bilirubin toxicity and may be of relevance in neonates affected with severe hyperbilirubinemia.